Study of the effect of the VEGF receptor blockade on the antiischemic activity of the compound GK-2 in a rat hind limb ischemia model - E. S. Pekeldina; I. A. Miroshkina; A. V. Sorokina; N. M. Sazonova; M. B. Vititnova; S. A. Kryzhanovskiy (Фармакокинетика и Фармакодинамика)
Earlier, in experiments in vitro and in vivo, it was shown that the TrkA receptor agonist compound GK-2, which was a low molecular weight NGF mimetic, had pronounced angiogenic and antiischemic activity. However, it remained unclear whether this activity was associated with the activation of VEGF-A, since, on the one hand, there are reports that NGF-mediated angiogenesis can be initiated by activating NGF of the vascular endothelial growth factor VEGF-A, and on the other hand, it is shown that a selective antagonist of Flk1 receptors specific for VEGF-A, compound SU-5416 does not affect the angiogenic effect of NGF. Purpose of the investigation. Study of the selective VEGF blockade effect on the antiischemic activity of the TrkA receptor agonist GK-2. Methods. Evaluation of the compound GK-2 antiischemic activity was assessed in model experiments simulating hind limb ischemia in rats. Results. It has been shown that against the background of blockade of VEGF-A binding with specific for it (VEGFR1 / Flt-1 / and VEGFR2 / KDR /) receptors, bevacizumab (2.5 mg / kg, i.p., every 3 days for 14 days) compound GK-2 (1 mg / kg, i.p., daily, for 14 days) realizes its antiischemic activity. Conclusion. The results of these experiments indicate that the selective blockade of VEGF does not significantly affect the anti-ischemic activity of the dipeptide NGF mimetic compound GK-2, which has the properties of a TrkA receptor agonist.